2020
DOI: 10.3390/nu13010047
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Strategies for Suppressing NLRP3 Inflammasome Activation: Pertinence to the Management of COVID-19 and Beyond

Abstract: Inflammasomes are intracellular protein complexes that form in response to a variety of stress signals and that serve to catalyze the proteolytic conversion of pro-interleukin-1β and pro-interleukin-18 to active interleukin-1β and interleukin-18, central mediators of the inflammatory response; inflammasomes can also promote a type of cell death known as pyroptosis. The NLRP3 inflammasome has received the most study and plays an important pathogenic role in a vast range of pathologies associated with inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 279 publications
1
31
0
1
Order By: Relevance
“…Several studies have shown that NLRP3 inflammasome is a potential therapeutic target for COVID-CS. 164 , 348 , 349 …”
Section: Blockade Of Signaling Pathwaysmentioning
confidence: 99%
“…Several studies have shown that NLRP3 inflammasome is a potential therapeutic target for COVID-CS. 164 , 348 , 349 …”
Section: Blockade Of Signaling Pathwaysmentioning
confidence: 99%
“…These include polyphenols, lipid extracts, and tomato-based nutraceuticals, all of which have been suggested for the potential prevention of cardiovascular complications of COVID-19, such as thrombosis (32,69). Melatonin is another supplement that has been identified as a potential antiviral agent against SARS-CoV-2 by computational methods (235), and it has also been highlighted as a potential therapeutic agent for COVID-19 due to its documented antioxidant, antiapoptotic, immunomodulatory, and anti-inflammatory effects (69,236,237). Notably, melatonin, vitamin D, and zinc have attracted public attention because they were included in the treatment plan of the former president of the United States upon his hospitalization due to COVID-19 (238).…”
Section: Discussionmentioning
confidence: 99%
“…Several nutraceuticals may also suppress the contribution of NLRP3 inflammasomes to many inflammation-linked pathologies. Amongst them are lipoic acid, ferulic acid, melatonin, phycocyanobilin, berberine, N-acetylcysteine, glucosamine, taurine, folate, vitamin B12, and betaine [ 159 ]. There are also reports suggesting that some plant-derived compounds and Chinese herbal medicines have a neuroprotective effect in treating AD by attenuating the activation of the NLRP3 inflammasome pathway [ 160 ].…”
Section: Inflammasomes As a Possible Link Between Inflammation-associated Peripheral And Brain Insulin Resistance In Metabolic Disease Anmentioning
confidence: 99%